The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1080/02786826.2012.762973
|View full text |Cite
|
Sign up to set email alerts
|

Development and Performance Evaluation of an Exhaled-Breath Bioaerosol Collector for Influenza Virus

Abstract: The importance of the aerosol mode for transmission of influenza is unknown. Understanding the role of aerosols is essential to developing public health interventions such as the use of surgical masks as a source control to prevent the release of infectious aerosols. Little information is available on the number and size of particles generated by infected persons, which is partly due to the limitations of conventional air samplers, which do not efficiently capture fine particles or maintain microorganism viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 28 publications
2
71
0
Order By: Relevance
“…It is not yet known whether the low recovery of infectious virus (despite high copy numbers of viral RNA) represents technical difficulties in sampling and culturing exhaled breath samples or whether the vast majority of the virus exhaled by influenza A patients is actually non-infectious. These findings are consistent with those by Lindsley et al [23] We designed the sampler specifically to overcome problems with existing bioaerosol samplers, including efficiently collecting sub-micron particles into a liquid and use of appropriate buffer to preserve infectiousness [27]. We have previously shown that collection on solid, dry collection media resulted in large losses of culturability [26].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…It is not yet known whether the low recovery of infectious virus (despite high copy numbers of viral RNA) represents technical difficulties in sampling and culturing exhaled breath samples or whether the vast majority of the virus exhaled by influenza A patients is actually non-infectious. These findings are consistent with those by Lindsley et al [23] We designed the sampler specifically to overcome problems with existing bioaerosol samplers, including efficiently collecting sub-micron particles into a liquid and use of appropriate buffer to preserve infectiousness [27]. We have previously shown that collection on solid, dry collection media resulted in large losses of culturability [26].…”
Section: Discussionsupporting
confidence: 75%
“…We collected exhaled breath with the subject seated in front of the inlet for a sampler designed for human exhaled breath collection, Figure 2, (G-II) described in detail by McDevitt et al [27] Briefly, the G-II inlet was cone shaped so that the subject's face was situated inside the large end of an open cone with air drawn continuously around the subject and into the sampler. The cone allows the subject to breathe normally and unlike use of a mouthpiece, the subject could also wear a mask.…”
Section: Methodsmentioning
confidence: 99%
“…By comparison, the system used by Milton et al . collects aerosols produced by natural coughs and exhalations over a 30‐minute period, and that group has reported greater success in detecting and quantifying airborne influenza virus 19, 25, 38. Thus, our results suggest that future work studying infectious aerosol production and the presence of infectious aerosols in the environment should collect sample volumes that are as large as practically possible, which would likely entail using high sample flow rates and long sample times.…”
Section: Discussionmentioning
confidence: 74%
“…droplets) and bioaerosols (bacteria, viruses, fungi) that derive from the respiratory tract (8,9). Droplets of respiratory tract lining fluid (RTLF) are released from the surfaces of the airways (Figure 2A).…”
Section: Preanalytical Phase Of Ebc Analysismentioning
confidence: 99%